2017
DOI: 10.3926/jiem.2313
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and psychological factors in 5S and total productive maintenance

Abstract: Abstract:Purpose: The purpose of this paper is to investigate the role of ethical and psychological factors in the implementation of 5S and TPM at cement plants in Kurdistan Region of Iraq.Design/methodology/approach: The mixed methods represented in a questionnaire survey and semi-structured interviews for data collection in the framework of the case study were chosen. The questionnaire survey already has been tested. Findings:The findings of this paper revealed that ethical factors had a larger role than psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The results presented here confirm and reinforce the findings, found in the literature, which establish a relation between the level of employee motivation during TPM implementation and results in terms of operational performance (Jain et al, 2018;Kareem & Amin, 2017;Bamber et al, 1999;Attri et al, 2013;Sharma et al, 2016). The relation between motivation and performance has been studied in other contexts related to manufacturing, with similar results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results presented here confirm and reinforce the findings, found in the literature, which establish a relation between the level of employee motivation during TPM implementation and results in terms of operational performance (Jain et al, 2018;Kareem & Amin, 2017;Bamber et al, 1999;Attri et al, 2013;Sharma et al, 2016). The relation between motivation and performance has been studied in other contexts related to manufacturing, with similar results.…”
Section: Discussionsupporting
confidence: 90%
“…Jain et al (2018) show evidence that employee motivation, along with other human-related factors is a key enabler for TPM implementation. Kareem & Amin (2017) studied the role of psychological and ethical factors in the implementation of TPM and concluded that employee motivation and morale is an important factor to enable success. Bamber et al (1999) studied TPM implementation in UK manufacturing organizations and concluded that workforce and management motivation are key success factors.…”
Section: The Role Of Motivation In the Performance Of Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…• If the Confirmatory Composite Analysis approach (Henseler, 2017a;Schuberth et al, 2018a) is compatible with recent proposals made about the Confirmatory Tetrad Analysis (CTA) (Gudergan, Ringle, Wende & Will, 2008;Tabet, Lambie, G.W., Jahani, S., & Rasoolimanesh, 2019a. This would allow us to analyse the measurement models of the operational definitions of latent variables; e.g., the skills of a job post that a worker masters, Total Production Maintenance (TPM) (Kareem & Amin, 2017;Marin-Garcia & Mateo-Martínez, 2013;Reyes, Alvarez, Martinez & Guaman, 2018), Lean Manufacturing, or the AMO model (Benet-Zepf, Marin-Garcia & Küster, 2018;Marin-Garcia & Martinez-Tomas, 2016). This would allow us to discern if they are "cultural" dimensions and if they exist themselves (and can, thus, explain organisational performances in the same way as personality exists and explains people's conducts).…”
Section: Discussionmentioning
confidence: 97%
“…The methods used for the data collection were structured interviews and questionnaire surveys. The comprehensive implementation of 5S and TPM was carried out based on the results of this study (Kareem & Amin, 2017). The benefits of TPM implementation in the sewing process are also well recognized.…”
Section: Introductionmentioning
confidence: 99%